Devidend payment behaviour and its determinants: The Malaysian property sector - Fadhirul Hisham, Aziz (2014)
Disappearing dividend phenomenon remains unexplored in the Malaysian market. Therefore, this study investigates whether or not the phenomenon exists in the Malaysian property sector. This is achieved by observing dividend pattern in the sector between 2000 to 2013. The study investigates dividend payout in the sector further by examining the factors that influence companies‟ decision to pay or not to pay dividends. Trend analysis was used to describe the dividend pattern over the period while logistic regression analysis was conducted to determine the factors that influence companies‟ payout decisions. Findings revealed an upward trend in the amount of dividends distributed in the sector over the period as well as in the number of dividend payers. The study provides evidence of dividend concentration in the property sector of Bursa Malaysia as results shows that a large portion of dividend paid out for all the years come from the top 10 payers. As revealed by the findings, the explanatory factors for dividend payout decisions in the Malaysian property sector include dividend premium, retained earnings to total equity, profitability, size, leverage, and past year dividend. Thus, findings of the study provide support for catering theory, lifecycle theory and dividend smoothing theory. Findings indicate that investment opportunities and crisis do not play any significant role in explaining payout decisions in the sector